الرحلة نحو التربية الجنسية الشاملة في تونس: بين السياقين الدولي والوطني من 1956 إلى 2011 م. - الزوالي، مصطفى الشيخ (مركز الأبحاث والدراسات التربوية, 2022)
انطلقنا في هذه الدراسة من التساؤلات المطروحة في الجدل، الذي أثاره إعلان وزارة التربية في تونس، أواخر سنة 2019، عن برنامجها لإدماج ما سمي بالتربية على الصحة الجنسية في المناهج التربوية. ونسعى من خلالها، إلى دراسة التطورات التي عرفها مفهوم التربية الجنسية والمفاهيم القريبة منه، في المجتمعات الغربية ولدى المنظمات الدولية المعنية، وتتبع المراحل المختلفة للتجربة التونسية في هذا المجال، بين السياقين الدولي والمحلي منذ 1956 إلى الوقت الراهن. In this study, we proceeded from the questions raised in the controversy, which was raised by the announcement of the Ministry of Education in Tunisia, at the end of 2019, about its program to integrate the so-called sexual health education into the educational curricula. Through it, we seek to study the evolution of the concept of sex education, and the concepts that are close to it, in Western societies and the international organizations concerned, and to trace the different stages of the Tunisian experience in this field, between international and local contexts from 1956 to the present day.
Keywords: المجتمع التونسي -- المناهج التربوية -- التربية الجنسية -- التربية الأخلاقية -- الفكر الغربي -- المنظمات الدولية